Dapansutrile in multidisciplinary therapeutic applications: mechanisms and clinical perspectives - Bai, Fuwei; Wang, Dongyang; Wu, Yingying (Frontiers in Pharmacology, 2025)
Dapansutrile, an orally active and selective NLRP3 inflammasome inhibitor, exerts its effects by directly binding to the NLRP3 NACHT domain. This action disrupts inflammasome assembly and caspase-1 activation, thereby inhibiting the maturation and release of the pro-inflammatory cytokines IL-1β and IL-18. Beyond this core inhibition, dapansutrile modulates immune cell chemotaxis and inhibits pyroptosis. Preclinical and clinical studies demonstrate its efficacy in mitigating pathology in diverse conditions, including gouty arthritis, cardiovascular diseases, neurodegenerative disorders, inflammatory bowel disease, and periodontitis. A favorable safety profile distinguishes it from other NLRP3 inhibitors like MCC950, with no significant hepatotoxicity reported in trials. Furthermore, dapansutrile exhibits synergistic effects when combined with agents such as lonafarnib or immune checkpoint inhibitors, enhancing anti-inflammatory and anti-tumor responses. This review consolidates evidence on dapansutrile’s molecular mechanisms, therapeutic applications, and biosafety, highlighting its potential as a novel, well-tolerated, and versatile anti-inflammatory agent. Future research should focus on optimizing its delivery, particularly to the central nervous system, and leveraging artificial intelligence to predict effective drug combinations.